Intersection of understanding: the digital, tactile and physical in fabric architecture - Kindt, Anna; Fisher, Amy; Fox, Erin; Donofrio, Mark (ARCC Conference Repository, 2014)
The use of tensile fabric in architecture results in structures that can be both ecologically sensitive and delight the eye ” but how do we begin to understand this nontraditional method of defining form and shaping space? Various methods of form finding help in understanding the capabilities of tensile fabric structures. Digital modeling, soap bubbles and stretchable fabrics can assist in understanding the inherent properties of fabric and the natural curvatures formed by the interaction of structure and fabric. These methods, however, are plagued by a steep learning curve and time investment that deters designers from utilizing fabric and makes it difficult to intuitively understand the properties of fabric. This paper explores how our group utilized a full-scale fabric installation meant to educate the user about the possibilities of fabric in architecture through an interactive and tactile experience. This study documented the users’ initial knowledge and comfort level with fabric in architectural applications as well as their understanding of its material properties and compared this understanding to their understanding after interacting with the installation. The results of this study show how the use of a hybrid methodology of exploring a new material can lead to an increased understanding of how to utilize fabric for architectural applications and form finding.